Analisis finansial budidaya rumput laut (eucheuma cottonii) di Kelurahan Teritip Kecamatan Balikpapan Timur Kota Balikpapan: Seaweed (Eucheuma cottonii) cultivation financial analysis in Balikpapan East Village District, Balikpapan City - Taufik; Fitriyana; Zul Asman Randika (Jurnal Ilmu Perikanan Tropis Nusantara (Nusantara Tropical Fisheries Science Journal), 2022)
This aims of research where to analysis profitability of seaweed farming in the village Teritip financially based investment criteria, namely: Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (Net B / C), Payback Period, and sensitivity analysis. this is study to knowing the marketing channel and the problems faced in the cultivation of seaweed in the Village. This is study was conducted from to January 2013 through March 2013. Method used the purposive sampling. Data analysis used financial analysis, (Present Net Value, Internal Rate of Return, Net Benefit Cost Ratio, Payback Period), and sensitivity analysis, and descriptive analysis for marketing level channels. Result of the research shows that the cultivation of seaweed in the Village Teritip was profitable. Seaweed cultivation was can be continue based on the indicator of NPV, IRR, Net B/C, Payback Period, and sensitivity analysis. Channel marketing was the use channel level one and level three, level at marketing purposes to Balikpapan and Surabaya.